ANALISIS KONTRASTIF KOPULA BAHASA INDONESIA DENGAN BAHASA INGGRIS - Dyah Kusumastuti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
Indonesia has its national language which is used in daily life. The national language becomes the part of curriculum taught in schools. However, English is also taught since elementary schools until college. It has sought as a compulsory subject. Since English is not spoken in daily life, the students feel difficult to master English well. The first language affected their English learning. The solution to the problem is that teacher should have fruitful strategy to teach English to the students. Having contrastive analysis of copula will be useful for the teachers. They will be able to understand the different things appeared among the two languages. Moreover, they will know what methods and techniques appropriate for them to apply in their class. Keywords: contrastive analysis, copula, English teaching